2021
DOI: 10.1093/ee/nvab040
|View full text |Cite
|
Sign up to set email alerts
|

Landscape Effects on Native Bees (Hymenoptera: Anthophila) Captured in Pheromone Traps for Noctuid Crop Pests (Lepidoptera: Noctuidae)

Abstract: Noctuid pests, including tobacco budworm (Chloridea virescens (Fab.)) and bollworm (Helicoverpa zea (Boddie)), are significant pests of southern row crops including cotton (Gossypium hirsutum L.), corn (Zea mays L.), and soybean (Glycine max (L.) Moench.). This pest complex is seasonally monitored through Hartstack traps that are baited with synthetic lepidopteran pheromones across the southern United States. We examined bycatch from the noctuid traps deployed across the Mississippi Delta in 2015, 2016, and 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 50 publications
0
7
0
1
Order By: Relevance
“…(2016) and U.S. Department of Agriculture, Animal and Plant Health Inspection Service, Cooperative Agricultural Pest Survey approved methods for pest surveillance (Cooperative Agricultural Pest Survey [CAPS], 2022). Previous research identified that bumble bees are attracted to pest monitoring traps and suggested that these captures be used to advance knowledge of biodiversity, population fluctuations, and other ecological objectives (Buchholz et al., 2011; Christman, Spears, Strange, et al., 2022; Grocock et al., 2020; Grocock & Evenden, 2020; Parys et al., 2021; Sipolski et al., 2019; Spears et al., 2016, 2021; Spears & Ramirez, 2015; Whitfield et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(2016) and U.S. Department of Agriculture, Animal and Plant Health Inspection Service, Cooperative Agricultural Pest Survey approved methods for pest surveillance (Cooperative Agricultural Pest Survey [CAPS], 2022). Previous research identified that bumble bees are attracted to pest monitoring traps and suggested that these captures be used to advance knowledge of biodiversity, population fluctuations, and other ecological objectives (Buchholz et al., 2011; Christman, Spears, Strange, et al., 2022; Grocock et al., 2020; Grocock & Evenden, 2020; Parys et al., 2021; Sipolski et al., 2019; Spears et al., 2016, 2021; Spears & Ramirez, 2015; Whitfield et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The details for all methodological and analytical steps are described in detail in the following sections. (Buchholz et al, 2011;Parys et al, 2021;Sipolski et al, 2019;Spears et al, 2016Spears et al, , 2021Spears & Ramirez, 2015;Whitfield et al, 2019).…”
Section: Overviewmentioning
confidence: 99%
“…Bumble bees were collected within pest monitoring traps that were placed by state cooperators in agricultural fields across diverse regions in the USA as part of early-detection surveys for invasive lepidopterans following Spears et al, (2016) and U.S. Department of Agriculture, Animal and Plant Health Inspection Service, Cooperative Agricultural Pest Survey approved methods for pest surveillance (CAPS, 2022). Previous research identified that bumble bees are attracted to pest monitoring traps and suggested that these captures be used to advance knowledge of biodiversity, population fluctuations, and other ecological objectives (Buchholz et al, 2011; Spears and Ramirez, 2015; Sipolski et al, 2019; Whitfield et al, 2019; Grocock et al, 2020; Grocock and Evenden, 2020; Parys et al, 2021; Spears et al, 2016, 2021; Christman et al, 2022a).…”
Section: Methodsmentioning
confidence: 99%
“…Within agricultural systems, intensification and expansion of high-yielding field crops have led to extensive reductions in landscape composition (i.e., the number and amount of distinct land cover categories) and configuration (i.e., the spatial arrangement of those land cover categories), resulting in landscape simplification (Meehan et al, 2011; Pfeiffer et al, 2019; Nelson and Burchfield, 2021). Landscape simplification often reduces the availability, diversity, and distribution of nutritionally sufficient floral resources and nesting sites for bumble bees (Parys et al, 2021), leading them to be inadvertently extirpated in these agricultural environments (Westphal et al, 2003; Hall et al, 2017; Williams et al, 2012). While bumble bees can fly several kilometers to establish colonies and forage, they are also central place foragers with strong site fidelity (Goulson, 2010; Lepais et al, 2010; Rao and Strange, 2012; Ogilvie and Thomson, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…надавали перевагу блакитним пасткам [11]. У дослідженнях з феромонними пастками Hartstack, які не мають кольорових ознак, не відмічалось різниці привабливості для бджіл у порівнянні з білими пастками, тому дослідниками зроблено припущення про існування інших причин окрім візуальних [12].…”
Section: результати дослідженняunclassified